The Mediating Role of Perceived Value in the Relationship between Audit Service Quality and Auditee Satisfaction: Peran Perceived Value dalam Memediasi Pengaruh Kualitas Layanan Audit terhadap Kepuasan Auditee pada Divisi Audit Internal Konstruksi, Pembangkitan, dan Energi Baru Terbarukan - Zulhendrianto Zulhendrianto; Khairani Ratnasari Siregar (Fakultas Seni Rupa dan Desain ITB, 2026)
The growing complexity of organizational governance and risk management has shifted the role of internal audit from a mere control mechanism to a strategic partner. Although previous studies have extensively examined audit quality from compliance and financial reporting perspectives, limited attention has been given to how auditees perceive the value created by internal audit services, particularly within strategic stateowned enterprises implementing purpose-driven internal audit. This study investigates the influence of audit service quality on auditee satisfaction, mediated by perceived value, within the Internal Audit Division for Construction, Generation, and Renewable Energy at PT PLN (Persero). Using a quantitative approach, five dimensions of audit service quality—tangibles, reliability, responsiveness, assurance, and empathy—were analyzed using partial least squares structural equation modeling (PLS-SEM). This study addresses this research gap by positioning perceived value as a psychological mechanism linking audit service quality and auditee satisfaction. The results demon strate that all dimensions significantly impact perceived value, which in turn mediates their effect on satisfaction. Responsiveness and empathy were found to be the most dominant influences. These findings support the practical implementation of a purposedriven internal audit model that prioritizes stakeholder value perception. This study contributes to the theoretical development of audit service quality and perceived value in public sector enterprises, particularly in trust-based professional contexts.